PENGELOLAAN ARSIP PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN PONOROGO TAHUN 2020 - Wavy Nurrohmah (Master of Public Administration, Universitas Slamet Riyadi, 2021)
Archive has a role as a memory center, a source of information as well as amonitoring tool that is indispensable in every organization. The research methodused is descriptive qualitative. Data collection techniques using interviews anddocumentation. The sampling technique in this study used purposive sampling sothat there is a key informant and four people as supporting informants. The dataanalysis technique used an interactive analysis model (Miles and Huberman). Theresults obtained conclusions, namely: 1) archive management has beenimplemented in accordance with existing procedures which include budgetplanning, activity program planning, and financial accountability. 2) The Libraryand Archives Service has been running well The coordination of activities bothvertically and horizontally runs smoothly. Socialization about archiving is alsoroutinely carried out both internally at the Library and Archives Service as well asto all OPDs in the Ponorogo District Government with the material presentedcovering the theme of archival governance. 3) Actuating has been routinely carriedout at the Library and Archives Service. This can be seen from the directives thatare routinely carried out by the leadership both in direct meetings with employeesand daily briefings in the official whatsapp group. 4) Internal archives supervisionis carried out by the district's internal archives supervision team, while externalarchives supervision is carried out once a year by the archives supervision team.from the Province.Keywords: Planning, Organizing, Actuating, Controlling